A microfluidic Lab-on-a-Disc (LOD) for antioxidant activities of plant extracts - Rahman, Nurhaslina Abd; Ibrahim, Fatimah; Aeinehvand, Mohammad Mahdi; Yusof, Rohana; Madou, Marc J. (MDPI, 2018)
Antioxidants are an important substance that can fight the deterioration of free radicals and can easily oxidize when exposed to light. There are many methods to measure the antioxidant activity in a biological sample, for example 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant activity test, which is one of the simplest methods used. Despite its simplicity, the organic solvent that has been used to dilute DPPH is easily evaporated and degraded with respect to light exposure and time. Thus, it needs to be used at the earliest convenient time prior to the experiment. To overcome this issue, a rapid and close system for antioxidant activity is required. In this paper, we introduced the Lab-on-a-Disc (LoD) method that integrates the DPPH antioxidant activity test on a microfluidic compact disc (CD).We used ascorbic acid, quercetin, Areca catechu, Polygonum minus, and Syzygium polyanthum plant extracts to compare the results of our proposed LoD method with the conventional method. Contrasted to the arduous laborious conventional method, our proposed method offer rapid analysis and simple determination of antioxidant. This proposed LoD method for antioxidant activity in plants would be a platform for the further development of antioxidant assay.